Development of solar assisted membrane distillation system using solar thermal collector - Mohd Amirul Hilmi, Mohd Hanoin (2022)
The increase in freshwater demand and environmental pollution is leading to an increase in the use of renewable energy for the seawater desalination system. One fast-growing seawater desalination technology is solar assisted membrane distillation (SAMD), which can address the shortage of fresh water without increasing the cost of electricity. However, the present technology did not study the thermal performance of the SAMD system and simply used the commercial solar thermal collector (STC) during the experiments. The objective of this study is to evaluate the performance of in-house made SAMD system for seawater application in terms of the separation performance and energy sustainability under the Malaysian weather condition. In this work, Flat Plate Solar Thermal Collector (FPSC) system was designed to obtain the high thermal performance by varying the tube diameter (D = 3/4-inch and 3/8-inch), pipe spacing (S =18.5 cm and 27.0 cm) and inlet mass flow rates (0.01 - 0.05 kg/s). After choosing the best FPSC design, the system was then integrated into the direct contact membrane distillation system (DCMD) for sea water testing. The FPSC functions as a preheating of the simulated and actual seawater feed solution for indoor assessment before testing under direct sunlight. 2.5 wt.% of sodium chloride (NaCl) was used as the simulated seawater represents the standard seawater. In this work, fouled membranes were also analyzed for the scaling tendency using scanning electron microscopy (SEM) with energy dispersive X-Ray (EDX). For the design part, it can be observed that the pipe collector with tube diameter of 3/4-inch obtained better thermal performance and collector efficiency as compared to the 3/8-inch tube diameter, which recorded of 3.5% and 9.4% increment, respectively. Meanwhile, 18.5 cm pipe spacing was 4.3% and 12.6% higher in thermal performance and collector efficiency, respectively, compared to 27 cm pipe spacing. In term of inlet mass flow rate, the optimum mass flow rate is 0.03 kg/s with a radiation intensity ranging from 250 to 1050 W/m2. The best design based on the three parameters was then used and coupled with the DCMD system for indoor and outdoor analysis using seawater. For the outdoor evaluation, the SAMD system was analyzed under sunny and cloudy weather. The maximum permeate flux when the system was operated under direct sunlight is 4.35 kg/m²h. With respect to the salt rejection, 99.9% rejection was achieved in all experiments and the permeate was compared to standard drinking water. Although the final permeate quality is comparable to that of drinking water, some impurities were detected during the SEM-EDX analysis. It can be concluded that the manufactured SAMD system can be a green technology option in seawater desalination because it requires only a minimum electricity from the power grid.